Virgin widows - Gu, Hua (Fiction from modern China., 1996)
Things just keep getting better and better. ... Well, don't they? If you are a woman and you live in China, to answer this question you will need not only to look around you but to look back, to see not just how things are now but how they once were. China has traveled a long and torturous road since the collapse of the final imperial dynasty and the establishment of a modern republic early in this century; but have the nature of women's lives and their opportunities for just and equal treatment improved? Renowned writer Gu Hua confronts this issue in Virgin Widows, a poignant and disquieting novel that unfolds in alternating chapters the stories of two women whose lives, despite being separated by nearly a century, reveal a disturbing similarity. First published in China in 1985, it appears now in English for the first time.